2022
DOI: 10.21931/rb/2022.07.04.38
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic effect of sunflower residues on some soil properties and growth parameters of wheat, bean and flax crops

Abstract: Allelopathic effects of the sunflower verities Helianthus annuus residues were evaluated on some soil properties and their potential against growth parameters of the proposed successive crops Wheat Triticum aestivumL., Broad Bean Vicia fabe L. and Flax Linum UstatissmimL. Sunflower plants were chopped and incorporated with field soil after getting seed, and then successive crops were cultivated. The sunflower residues have reinforced the soil with the macronutrients considered essential for the germination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…The residual suppression effect of sunflowers plants also persisted in the next crop for up to 75 days. Another field experiment indicated that sunflower residues incorporated into the field soil significantly inhibited the total number and biomass of weeds growing in the wheat field [20]. The best allelopathic effects of the three sunflower genotypes based on the current study were observed when the wheat crop was cultivated in the same area as a successive crop as compared with the other crops; broad bean and flax.…”
Section: Weed Densitymentioning
confidence: 58%
“…The residual suppression effect of sunflowers plants also persisted in the next crop for up to 75 days. Another field experiment indicated that sunflower residues incorporated into the field soil significantly inhibited the total number and biomass of weeds growing in the wheat field [20]. The best allelopathic effects of the three sunflower genotypes based on the current study were observed when the wheat crop was cultivated in the same area as a successive crop as compared with the other crops; broad bean and flax.…”
Section: Weed Densitymentioning
confidence: 58%
“…Sunflower is an allelopathic plant which possesses many chemical compounds that can actively influence the growth of surrounding plants (Debaeke et al, 2021;Nafees et al, 2021a;Flayyih, Almarie, 2022). These chemical compounds known as allelochemicals act through direct interference with physiological functions of receptor plants such as seed germination, root growth, and shoot growth (Kupidłowska et al, 2006;Oliwa et al, 2017;Lalchand et al, 2021;Okrushko, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It was investigated that extracts of sunflower reduce seed germination and seedling growth of many successive plants (Bashir et al, 2017;Ullah et al, 2017;Sarvadamana et al, 2019;Ravlić et al, 2022). Sunflower residues negatively affect plant development and nutrient accumulation in some plants (Gawronska et al, 2007;Morais et al, 2014;Flayyih, Almarie, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason for this may be allelochemical inhibition. Allelochemicals diminish nutrients and water absorption by roots [29] and suppress photosynthesis and respiration [3,30,31].…”
Section: Introductionmentioning
confidence: 99%